Comparison of Ray Traced Based Models with Physical Optic Model - Tabakcıoğlu, Mehmet Barış (Ieee, 2016)
Electromagnetic wave propagation in free space is an excessively simplified situation. Hence, the vital question is how an electromagnetic wave propagates in ambient including obstructions like mountains, trees, hills or buildings. These obstructions reflect, diffract and scatter the electromagnetic waves. UTD and S-UTD models are ray-tracing-based electromagnetic wave propagation models and shortly explained in this paper. In addition, exhaustive information is supplied about the improved slope UTD model, is called the S-UTD-CH model. Electromagnetic wave propagation models, which are UTD, S-UTD, S-UTD-CH and PO, are compared with regard to prediction accuracy and computation time among themselves. Widespread simulation results are provided to compare the models in terms of prediction accuracy and computation time. Moreover, the S-UTD-CH model is considered an optimum model in terms of its accuracy and computation time. Furthermore, how the transmitter height, the distance between buildings and the operating frequency affects the relative path loss at the receiver are analyzed.
URSI-Commission-B International Symposium on Electromagnetic Theory (EMTS) -- AUG 14-18, 2016 -- Espoo, FINLAND
Keywords: [No Keywords]